The Effect of Green Accounting Implementation on CSR Disclosure in Indonesian LQ45 Banking Sector - Irham pakkawaru; Rizki Amalia; Dede Arseyani; Nuriatullah; Muh. Syafaat (Jurnal Ilmu Perbankan dan Keuangan Syariah, 2024)
This research examines the relationship between green accounting practices and corporate social responsibility disclosure (CSRD) in Indonesian banking institutions listed on the Indonesia Stock Exchange (IDX). The study covers the period from 2018 to 2021, focusing on banks that consistently published both annual reports and sustainability reports. The sample selection employed a purposive sampling technique to ensure data relevance and completeness. The research methodology utilized a quantitative approach, analyzing data from annual reports and sustainability reports of selected banks. Green accounting implementation was measured using dummy variables, where companies disclosing environmental costs in their annual reports were coded as 1, and those not disclosing were coded as 0. Corporate social responsibility disclosure was assessed using standardized disclosure metrics. Simple regression analysis reveals that green accounting implementation does not have a statistically significant effect on CSRD (t = -1.644, p = 0.118). The coefficient of determination (Adjusted R² = 0.082) indicates that green accounting explains only 8.2% of the variance in CSRD practices. However, the study finds a positive relationship between environmental performance and CSRD levels, suggesting that banks with better environmental performance tend to provide more comprehensive social responsibility disclosures. These findings contribute to the understanding of sustainability reporting practices in the Indonesian banking sector and highlight the need for stronger integration between environmental accounting and corporate social responsibility disclosure frameworks